2020
DOI: 10.1007/s11422-019-09968-1
|View full text |Cite
|
Sign up to set email alerts
|

The resurgence of everyday experiences in school science learning activities

Abstract: Science education can be alienating for students, as it is apart from the mundane world with which they are familiar. Science education research has approached the gap between everyday understandings and science learning largely as a challenge arising while learning about science concepts and the kinds of instructional approaches that may support this. However, the forms of everyday ways of relating to the world fundamentally expand beyond conceptual understandings. In this study, we use data from an outdoor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Therefore, it is very important to find out the attitude of students to these events in order to connect the student's daily personal experience with historical science through them. This approach has repeatedly become the subject of research by specialists in various fields of scientific knowledge [8]. Researchers focus not only on personally significant events for the student in the study of the subject, but in the interaction of the teacher, student and parents [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is very important to find out the attitude of students to these events in order to connect the student's daily personal experience with historical science through them. This approach has repeatedly become the subject of research by specialists in various fields of scientific knowledge [8]. Researchers focus not only on personally significant events for the student in the study of the subject, but in the interaction of the teacher, student and parents [14].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, this is the ability to work with information that comes through Internet resources. In modern society, young people are the most receptive social audience to the values, opinions, views expressed by the Internet space [7][8][9][10][11]. Even viewing of publications, blogs of science-dubious content is fraught with the danger of accepting these values, breaking the social and cultural identity, and the birth of extremist sentiments.…”
Section: Introductionmentioning
confidence: 99%
“…Despite challenges, the participating teachers tried to be innovative within their contexts. Teacher M was an advocate for using real-life situations as a platform for learning and understanding concepts (as also described by Kervinen et al, 2020). He used local newspapers, the television news and family discussions about present environmental situations to reinforce teaching: It's very important that learners are not passive within the class, they need to be active.…”
Section: Resourcefulness In Teaching Practicementioning
confidence: 99%
“…Thus, connecting the scientific inquiry with the everyday forms of relating to the world could allow the students to students engage in doing science in ways that are meaningful in their everyday lives (cf. Kervinen et al, 2020b;Ko, 2021).…”
Section: Envisioning Alternative Scenarios and Narrativesmentioning
confidence: 99%
“…The findings of this study also show how students reframed the uncertainty through the integration of their everyday experience in the inquiry processes. Integration of everyday forms of knowing in science teaching is essential to make it meaningful for the students (e.g., Archer et al, 2010;Ko, 2021), and it has been shown that the absence of a teacher in particular can enable such connections particularly well (Kervinen et al, 2020b). The present study extends the previous work by showing how the students used their everyday experiences and understandings of urban life as a resource to manage uncertainty that is meaningful not only for themselves but also regarding the production of new knowledge of the world.…”
Section: Students Reframe Uncertaintymentioning
confidence: 99%